Psychological Features of Deviant Behavior in Adolescents - Abdukakhhorova Gulnoza Abdurasulovna (Researchparks Publishing, 2022)
Definition of the role of socio-psychological services in the elimination of deviant behavior in adolescents, they have identified psychological factors leading to deviant behavior, and changes that occur as a result of the process of deviant behavior.